Effect of Cardiac Rehabilitation Program on Blood Coagulation in Patients with Post cardiac Valvular Replacement at Naresuan University Hospital - Paorod, Phawinee; Sayasathid, Jarun; Chidnok, Weerapong (Journal of The Royal Thai Army Nurses, 2021)
The objective of this study was to investigate the effects of cardiac rehabilitation program on blood coagulation parameters and the relationship between blood coagulation parameters and exercise capacity in patients after cardiac valve surgery. In quasi experimental study, one hundred and nineteen patients who underwent heart valve surgery at Naresuan University hospital since January 2015 until December 2018 were participated in this study.The patients were divided into 2 groups by convenience sampling (Training group (n = 99) and Control group (n = 20)).The training group had completed the cardiac rehabilitation program before discharge and 12 weeks after discharge at home.The control group had performed the cardiac rehabilitation program before discharge from hospital.The six-minute walk test and blood coagulation parameters were assessed before discharge and at 12 weeks after discharge.The results showed that there were no different in targets blood coagulation parameters between groups before discharge from the hospital (P> .05). The training group had significantly higher in targets blood coagulation parameters and six-minute walk distance than the control group at 12 weeks after discharge (P<.05).This study reveals that home based cardiac rehabilitation program can improve the targets of blood coagulation parameters in patients with post heart valve surgery.